2021
DOI: 10.1088/1748-605x/abb875
|View full text |Cite
|
Sign up to set email alerts
|

Biomanufacturing organized collagen-based microfibers as a Tissue ENgineered Device (TEND) for tendon regeneration

Abstract: Approximately 800, 000 surgical repairs are performed annually in the U.S. for debilitating injuries to ligaments and tendons of the foot, ankle, knee, wrist, elbow and shoulder, presenting a significant healthcare burden. To overcome current treatment shortcomings and advance the treatment of tendon and ligament injuries, we have developed a novel electrospun Tissue ENgineered Device (TEND), comprised of type I collagen and poly(D,L-lactide) (PDLLA) solubilized in a benign solvent, dimethyl sulfoxide (DMSO). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The injection in the rabbit AT injury model revealed that LP-PRP and LR-PRP improved AT recovery more than LP-PRP ( Yan et al, 2017 ). Maghdouri-white et al developed a novel type of TEND consisting of PDLLA and type I collagen ( Maghdouri-White et al, 2021 ). For 2 weeks, annealed TEND rapidly adsorbs PRP and gradually releases PDGF-BB and TGF-β1.…”
Section: Tissue Regeneration Strategies For Achilles Tendon Injury Tr...mentioning
confidence: 99%
“…The injection in the rabbit AT injury model revealed that LP-PRP and LR-PRP improved AT recovery more than LP-PRP ( Yan et al, 2017 ). Maghdouri-white et al developed a novel type of TEND consisting of PDLLA and type I collagen ( Maghdouri-White et al, 2021 ). For 2 weeks, annealed TEND rapidly adsorbs PRP and gradually releases PDGF-BB and TGF-β1.…”
Section: Tissue Regeneration Strategies For Achilles Tendon Injury Tr...mentioning
confidence: 99%
“…TEND (Tissue Engineered Device), obtained by mixing type 1 collagen and PDLLA (poly DL-lactide) solubilized in DMSO (dimethyl sulfoxide), represents an effective solution. The morphological dimensioning of this structure allows improving cell adhesion, ensuring tissue integration and mechanical resistance [99].…”
Section: D) Ligament/tendonmentioning
confidence: 99%
“…Molecular alignment, fibrillary organisation, and covalent crosslinking of collagen molecules are key in dictating the macroscopic properties of specific biological tissues in vivo [1] and have been widely pursued for the development of functional collagen-based biomaterials and medical devices. In light of its major role in wound healing and tissue remodelling, collagen has therefore been successfully applied in wound dressings [3,4], guided bone regeneration membranes [5], tendon repair scaffolds [6], pelvic reconstruction meshes [7,8], as well as tracheal [9,10] and corneal [11] implants. Consequently, multiple design strategies, including blending with synthetic polymers [12], fibre spinning [13], and covalent crosslinking [14], have been developed for a range of collagen raw materials generating varying preclinical success.…”
Section: Introductionmentioning
confidence: 99%